INTERFERENSI BAHASA MELAYU TERHADAP BAHASA INDONESIA PADA TKI DI DUSUN GETAP KECAMATAN SURALAGA - Dian Aprila Diniarti; A. Amrulloh; S. Syahdan (PRASASTI: Journal of Linguistics, 2017)
Issues to be examined in this study is the cause of interference Malaysia language to Indonesian language performed by TKI Malaysia in subdistrict Suralaga and how is the form of interference against Indonesian Malay them. Malaysia migrant workers who had returned to his hometown Malaysia tends to insert language into the Indonesian language usage when they are invited to do  a conversation Indonesian. Based on these problems, the objectives of this research was to determine the causes and forms of language interference undertaken by TKI Malaysia in subdistrict Suralaga. This type of research is qualitative descriptive. While data collection techniques done by tapping and interview techniques. Data were recorded and then transcribed in writing and analyzed using the model of Miles and Huberman. Based on the analysis that has been done, it can be drawn the conclusion that the cause of the interference on TKI Malaysia language is social, the habit of using the Malay language when communicating, and the length of a migrant worker. While the forms of language interference that occurs is the interference of phonology, morphology, and syntax